4D phase-space acceptance of the quadrupole mass filter. Issue 3 (June 2017) - Konenkov, AN; Konenkov, NV; Verenchikov, AN
Simulations of the four-dimensional (4D) phase-space acceptance volume of a quadrupole mass filter (QMF) are discussed. The 4D acceptance is considered since the ion trajectories in the X and Y phase planes are dependent via the initial RF phase at ion entry into QMF. The QMF parameters are set up for resolution equal to the ion mass number M . For a wide range of ion masses, the acceptance is characterized by relatively large aperture with about 5% transmission, primarily defined by phase dependent ellipses. Contrary to expectations, the small-aperture central spot with 75% transmission accepts a very small portion, namely less than 1% of the passed through particles.